0 like 0 dislike
Which of the following equations is equivalent to 8(k + 11) - 6k = 19?

A. 2k + 11 = 19
B. 14k + 88 = 19
C. 14k + 11 = 19
D. 2k + 88 = 19​
by

2 Answers

0 like 0 dislike
D. 2k+88=19

Step-by-step explanation:

distribute the 8 to the k and 11, and you should get 8k +11 by multiplying the 8 to the k and 8 to the 11. now you have 8k+88-6k=19, and now you should combine like terms. 8k-6k=2k. so the answer is 2k+88=19
by
0 like 0 dislike
D no will be answer because 8 k plus 88 - 6k =19or , 2k -88 =19
by
Welcome to AskTheTask.com, where understudies, educators and math devotees can ask and respond to any number related inquiry. Find support and replies to any numerical statement including variable based math, geometry, calculation, analytics, geometry, divisions, settling articulation, improving on articulations from there, the sky is the limit. Find solutions to numerical problems. Help is consistently 100 percent free!

Questions

No related questions found